2013
DOI: 10.1097/01.sa.0000425547.06244.3f
|View full text |Cite
|
Sign up to set email alerts
|

Complex Procedural Skills are Retained for a Minimum of 1 Yr After a Single High-Fidelity Simulation Training Session

Abstract: T he random nature of adverse patient events and the vagaries of clinical exposure make assessment of pediatric anesthesia trainees complicated. Nonetheless, such assessment is critical to improving patient safety. In earlier studies, a multiple-scenario assessment offered reliable and valid measurements of the abilities of anesthesia residents. A set of relevant simulated pediatric perioperative scenarios was developed, and its effectiveness in assessing anesthesia residents and pediatric anesthesia fellows w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 1 publication
2
63
0
3
Order By: Relevance
“…11 In a separate study, however, Boet et al found that the skill can be retained for at least twelve months. 12 These studies were done on mannequins and did not focus on identifying the cricothyroid membrane. The average time that had elapsed since any surgical airway training in our study was more than one year for residents and nearly seven years for staff anesthesiologists.…”
mentioning
confidence: 99%
“…11 In a separate study, however, Boet et al found that the skill can be retained for at least twelve months. 12 These studies were done on mannequins and did not focus on identifying the cricothyroid membrane. The average time that had elapsed since any surgical airway training in our study was more than one year for residents and nearly seven years for staff anesthesiologists.…”
mentioning
confidence: 99%
“…To date, little research has been completed regarding this key issue. 7,12,[22][23][24][25] Much work in simulation retention has emphasized complex motor skills, such as cricothyroidotomy 22 and manipulation. 12 Although results from this work are promising, disagreement exists as decay in learning also has been documented.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Debriefing has been considered critical in helping explain retention of skills for up to a year. 23 In this research, debriefing was provided as well as a second opportunity to recreate the simulation to emphasize learning. This research differs from previous work in that the scenario emphasized private office decision-making, with lesser technical skills, such as AED administration.…”
Section: Discussionmentioning
confidence: 99%
“…Assumptions used were normal distribution of scores and a historical SD for the scores of 5.3 points. 46 …”
Section: Powermentioning
confidence: 99%